Spin transport at a Pt/InAs quantum well interface using spin Hall and Rashba effects - Jeon, Jeehoon; Kim, Seong Been; Kim, Taeyueb; Lee, OukJae; Han, Suk Hee; Kim, Hyung-jun; Koo, Hyun Cheol; Hong, Jinki (American Institute of Physics, 2020)
In the field of spintronics, charge-to-spin conversion without a ferromagnetic material has attracted intense interest from researchers seeking to realize a fully electrical spin device because this design obviates the need for magnetic field control of magnetization. Instead of spin injection from a ferromagnetic source, spin-Hall-induced pure spin current has recently attracted considerable interest for transferring spin information into the semiconductor channel. In the present work, the spin is injected from a platinum electrode via the direct spin Hall effect and is subsequently detected in a strong Rashba channel via the inverse spin Hall effect. Before being detected, the spin state is modulated by a gate voltage; the signal observed with various channel lengths and gate voltages demonstrates this Rashba precessional modulation. The addition of Zeeman precession induced by an external magnetic field provides the signal-elucidating definite spin motion in the channel and clear interplay between the Rashba and Zeeman processions. Our approach opens a fascinating possibility for realizing a ferromagnet-free system for use in low-power and high-temperature spin transistors.